Islamophobia in Belgium - Maréchal, Brigitte (Journal of Muslims in Europe, 2016)
This article represents one part of a vast research project undertaken between 2013 and 2015 on the reciprocal views Muslims and non-Muslims in Belgium, and particularly in Brussels, have of one another, and the relationships they maintain. It is above all a question of understanding how reciprocal tensions and adjustments are constructed. The various treatments the topic of Islamophobia receives represent one of them. Hence this article tries to evaluate the attitudes on each side with respect to this societal phenomenal and this concept. In addition to year-long observations carried out in Brussels, it is based on three evenings during which ten privileged interlocutors discussed this topic in-depth. Carried out before the Brussels attacks of March 22nd, 2016, this study provides a better grasp of how anxieties, or even a spiral of reciprocal accusations, are able to develop, and questions the uses of the category Islamophobia and its counterproductive character.